پنجاب کا جغرافیائی،تاریخی اورمعاشرتی پسِ منظر اورلسانی وادبی تناظرات: Geographical, Historical and Social Background and Linguistic and Literary Perspectives of Punjab - Abbas, Dr. Ansar; Hassan, Dr. Syed Zameer ul (Zoraiz, 2025)
In course of composition of comprehensive history of Urdu literature Punjab has served as a basic building block. The multidimensional approach with historical, geographical, social, linguistic and literary perspective is unavoidably necessary in the analysis of the contribution of the Punjab to the promotion of Urdu language. Notwithstanding all that contribution, Punjab school of thought has not enjoyed as much importance in history as has been done by Delhi school of thought and Lucknow school of thought on behalf of their political centrifugation. I dare say that the soil of Punjab is the depositary of enriching tradition in respect of Urdu literature. The outshining artists born on this soil have been serving as assets of Urdu literature. An attempt has been made to bring out the linguistic and literary perspective with reference to social and geographical aspects along with research paper.